EFFECTIVENESS OF THE APPLICATION OF THE PROBLEM BASED LEARNING MODEL BASED ON KAMPAR CULTURE TOWARDS IMPROVING STUDENTS' MATHEMATICAL REPRESENTATION ABILITIES - Endang, Endang Sri Sartika; Sartika, Endang Sri; Murni, Atma; Maimunah, Maimunah (Jurnal Gantang, 2025)
This research is motivated by the importance of mathematical representation ability. The results of the field study indicate that students' mathematical representation ability falls in the low category because they are not given the opportunity to develop their representations during the mathematics learning process. The purpose of this study is to determine the effectiveness of the Kampar culture-based Problem Based Learning model to improve students' mathematical representation ability. The Kampar culture used is traditional Kampar clothing, traditional Kampar games, traditional Kampar musical instruments, and traditional Kampar food. The study population is all students of SMA N in Bangkinang City; the sample of this study is grade X students of SMA N 2 Bangkinang City. The data collection technique used is the test technique. The data analysis techniques used are the normality test, the homogeneity test, the t-test, and the one-way ANOVA. The results of the study indicate that there is effectiveness in applying the Kampar culture-based PBL model to mathematical representation ability viewed from the overall students, and there is effectiveness in applying the Kampar culture-based PBL model to mathematical representation ability viewed from the level of students' abilities.